2020
DOI: 10.37201/req/120.2020
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for use of antigenic tests in the diagnosis of acute SARS-CoV-2 infection in the second pandemic wave: attitude in different clinical settings

Abstract: The high transmissibility of SARS-CoV-2 before and shortly after the onset of symptoms suggests that only diagnosing and isolating symptomatic patients may not be sufficient to interrupt the spread of infection; therefore, public health measures such as personal distancing are also necessary. Additionally, it will be important to detect the newly infected individuals who remain asymptomatic, which may account for 50% or more of the cases. Molecular techniques are the “gold standard” for the diagnosis of SARS-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
1
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 43 publications
(44 reference statements)
2
56
1
4
Order By: Relevance
“…The present study is the largest evaluation of the Panbio Ag-RDT in samples from symptomatic and asymptomatic patients in real-world context. This is a strength of our study because this is the setting where the majority of the patients with mild symptoms (up to 75%) 12 and close contacts are visited and followed-up. We incorporated COVID-19 testing into the usual care and management of patients with suspected SARS-CoV-2 infection and less than 2% of participants denied taking part in the study.…”
Section: Resultsmentioning
confidence: 99%
“…The present study is the largest evaluation of the Panbio Ag-RDT in samples from symptomatic and asymptomatic patients in real-world context. This is a strength of our study because this is the setting where the majority of the patients with mild symptoms (up to 75%) 12 and close contacts are visited and followed-up. We incorporated COVID-19 testing into the usual care and management of patients with suspected SARS-CoV-2 infection and less than 2% of participants denied taking part in the study.…”
Section: Resultsmentioning
confidence: 99%
“…Some authors have pointed out that, besides the lower sensitivity of Ag-RDTs compared to PCR, they improve the turnaround time for results, which is key to interrupt transmission chains in order to control the spread of this pandemic [ 6 , 7 , 21 , 22 ]. In line with this, some diagnostic algorithms recommend the use of these tests as the first step for symptomatic patients within the first five days after the onset of symptoms [ [21] , [22] , [23] ]. Our results support the use of CerTest and Panbio tests for that purpose.…”
Section: Discussionmentioning
confidence: 99%
“…After many countries had controlled the first wave of the pandemic, they relaxed their containment and physical distancing control measures, causing the infection rate to increase accordingly [ 3 , 4 ]. This worldwide resurgence of COVID-19 cases indicated that the second wave of the pandemic was occurring [ 5 7 ]. However, few studies have explored the effect of the second wave of the pandemic on mental health.…”
Section: Introductionmentioning
confidence: 99%